Integral membrane proteins significantly decrease the molecular motion in lipid bilayers: a deuteron NMR relaxation study of membranes containing myelin proteolipid apoprotein. - Meier, P (1987)
The influence of the myelin proteolipid apoprotein on lipid chain order and dynamics was studied by 2H NMR of membranes reconstituted with specifically deuterated dimyristoyl phosphatidylcholines. Quadrupolar echo and saturation recovery experiments were fitted by numerical solution of the stochastic Liouville equation, using a model that includes both inter- and intramolecular motions [Meier, P., Ohmes, E. & Kothe, G. (1986) J. Chem. Phys. 85, 3598-3614]. Combined simulations of both the relaxation times and the quadrupolar echo line shapes as a function of pulse spacing allowed unambiguous assignment of the various motional modes and a consistent interpretation of data from lipids labeled on the C-6, C-13, and C-14 positions of the sn-2 chain. In the fluid phase, the protein has little influence on either the chain order or the population of gauche rotational isomers but strongly retards the chain dynamics. For 1-myristoyl-2-[13-2H2] myristoyl-sn-glycero-3-phosphocholine at 35 degrees C, the correlation time for chain fluctuation increases from 20 nsec to 650 nsec and for chain rotation from 10 nsec to 180 nsec, and the gauche isomer lifetime increases from 0.15 nsec to 1.75 nsec, on going from the lipid alone to a recombinant of protein/lipid ratio 0.073 mol/mol. The results are essentially consistent with spin-label ESR studies on the same system [Brophy, P.J., Horvath, L.I. & Marsh, D. (1984) Biochemistry 23, 860-865], when allowance is made for the different time scales of the two spectroscopies.